MINORITISASI LGBT DI INDONESIA: CYBER BULLYING PADA AKUN INSTAGRAM @denarachman - Ragil Putri, Sukma Ari (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
Abstract:The evolution of technology made social media becomes excellent place for people to express themselves. One of those social media is Instagram. Instagram is a social media that allows users to upload their photos and then allow another person, including strangers, to comment on the photo. It then becomes a problem when the person who uses the Instagram is LGBT (Lesbian, Gay, Bisexual, Transgender). The photos were uploaded by LGBT become a medium for people to bully the LGBT. The purpose of this study was to determine how the forms of bullying that occur on LGBT’s Instagram and the dominant truth that underlying that bullying. This study used Queer Theory. Dominant truth possessed by society is related to the concept of binary opposition in which there are only two sex and two types of gender identity in this world. When there is another identity that blurs the line between the two, or a mix of both, then the identity is considered abnormal.